Guiding principles for rewilding - Steve Carver; Ian Convery; Sally Hawkins; Rene Beyers; Adam Eagle; Zoltan Kun; Erwin Van Maanen; Yue Cao; Mark Fisher; Stephen R. Edwards; Cara Nelson; George D. Gann; et al. (Conservation Biology, 2021)
There has been much recent interest in the concept of rewilding as a tool for nature conservation, but also confusion over the idea, which has limited its utility. We developed a unifying definition and 10 guiding principles for rewilding through a survey of 59 rewilding experts, a summary of key organizations’ rewilding visions, and workshops involving over 100 participants from around the world. The guiding principles convey that rewilding exits on a continuum of scale, connectivity, and level of human influence and aims to restore ecosystem structure and functions to achieve a self‐sustaining autonomous nature. These principles clarify the concept of rewilding and improve its effectiveness as a tool to achieve global conservation targets, including those of the UN Decade on Ecosystem Restoration and post‐2020 Global Biodiversity Framework. Finally, we suggest differences in rewilding perspectives lie largely in the extent to which it is seen as achievable and in specific interventions. An understanding of the context of rewilding projects is the key to success, and careful site‐specific interpretations will help achieve the aims of rewilding.

Long‐term monitoring of Serengeti bird species occurrence, abundance, and habitat - L. Francisco Henao-Diaz; Anthony R. E. Sinclair (Ecology, 2020)
The Serengeti ecosystem contains one of the most diverse bird assemblages in Africa. We present here a data set consisting of abundances of bird species in different habitats of the Serengeti ecosystem over a 87‐yr time frame. This data set comprises 66,643 georeferenced occurrences for 568 species from 1929 to 2017. Most records contain feeding location, food source, distribution status, and observation locality. The records originate from three different but complementary methodologies: points, sites, and transects. The point method (bird species records 1929–2017) is based on ad hoc observations and includes rare species or those in special habitats. These points came from published records as well from the research program of A. R. E. Sinclair and colleagues. The site method (1966–2017) is based on structured observations at sites selected to represent specific habitats, and replicated within habitats and over time. At each site, birds were recorded by sight and sound over a radius of 50 m for 10 min. The transect method (1997–2011) is based on road transects covering different areas of the ecosystem. Road transects were traversed using a vehicle with observers travelling at 30 km/h. Bird species were those easily seen from a vehicle out to 50 m either side. As most transects were traversed multiple times, this method provides information on temporal change in abundance for a select set of species. No copyright restrictions apply to the use of this data set other than citing this publication.

Thermal limits of summer-collected Pardosa wolf spiders (Araneae: Lycosidae) from the Yukon Territory (Canada) and Greenland - Susan E. Anthony; Christopher M. Buddle; Toke T. Høye; Brent J. Sinclair (Polar Biology, 2019)

Seeds in motion: Genetic assignment and hydrodynamic models demonstrate concordant patterns of seagrass dispersal - Elizabeth A. Sinclair; Leonardo Ruiz‐Montoya; Siegfried L. Krauss; Janet M. Anthony; Renae K. Hovey; Ryan J. Lowe; Gary A. Kendrick (Molecular Ecology, 2018)
Movement is fundamental to the ecology and evolutionary dynamics within species. Understanding movement through seed dispersal in the marine environment can be difficult due to the high spatial and temporal variability of ocean currents. We employed a mutually enriching approach of population genetic assignment procedures and dispersal predictions from a hydrodynamic model to overcome this difficulty and quantify the movement of dispersing floating fruit of the temperate seagrass Posidonia australis Hook.f. across coastal waters in south‐western Australia. Dispersing fruit cohorts were collected from the water surface over two consecutive years, and seeds were genotyped using microsatellite DNA markers. Likelihood‐based genetic assignment tests were used to infer the meadow of origin for seed cohorts and individuals. A three‐dimensional hydrodynamic model was coupled with a particle transport model to simulate the movement of fruit at the water surface. Floating fruit cohorts were mainly assigned genetically to the nearest meadow, but significant genetic differentiation between cohort and most likely meadow of origin suggested a mixed origin. This was confirmed by genetic assignment of individual seeds from the same cohort to multiple meadows. The hydrodynamic model predicted 60% of fruit dispersed within 20 km, but that fruit was physically capable of dispersing beyond the study region. Concordance between these two independent measures of dispersal provides insight into the role of physical transport for long distance dispersal of fruit and the consequences for spatial genetic structuring of seagrass meadows.

Genetic signatures of Bassian glacial refugia and contemporary connectivity in a marine foundation species - Elizabeth A. Sinclair; Janet M. Anthony; Dougal Greer; Leonardo Ruiz‐Montoya; Suzanna M. Evans; Siegfried L. Krauss; Gary A. Kendrick (Journal of Biogeography, 2016)
Aim To examine the population genetic structure in Posidonia australis meadows , a marine foundation species capable of long distance dispersal ( LDD ), and the role of historical versus contemporary processes in shaping post Last Glacial Maximum ( LGM ) re‐colonization. Location Southeastern Australia including the Bass Strait Islands. Methods We generated multilocus genotypes and assessed spatial patterns of genetic diversity. Relationships among meadows were assessed in terms of historical sea level changes, oceanic boundary currents and contemporary seed dispersal based on a hydrodynamic model. Results There was strong regional spatial genetic structuring among P. australis meadows in south‐eastern Australia, which was congruent with three recognized marine biogeographical provinces [Peronian (eastern), Flindersian (western and southern), and Maugean (south‐eastern)]. The genetic data suggest Maugean meadows persisted in isolation during the LGM , with evidence for admixture and contemporary gene flow. Simulated dispersal events identified high rates of local and regional demographic connectivity, with evidence for occasional LDD events. Main conclusions The strong regional differentiation is consistent with long‐term barriers to dispersal persisting in the marine environment through many sea level fluctuations. Bass Strait Island meadows all have strong signals of genetic admixture. A weak but significant isolation by distance relationship is consistent with a historical signal and contemporary seed dispersal mostly within the Bass Strait.

Thermal biology and immersion tolerance of the Beringian pseudoscorpion Wyochernes asiaticus - Susan E. Anthony; Christopher M. Buddle; Brent J. Sinclair (Polar Biology, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

The repeated bout effect of typical lower body strength training sessions on sub-maximal running performance and hormonal response - Kenji Doma; Moritz Schumann; Wade H. Sinclair; Anthony S. Leicht; Glen B. Deakin; Keijo Häkkinen (European Journal of Applied Physiology, 2015)

Planetary Stewardship in an Urbanizing World: Beyond City Limits - Sybil P. Seitzinger; Uno Svedin; Carole L. Crumley; Will Steffen; Saiful Arif Abdullah; Christine Alfsen; Wendy J. Broadgate; Frank Biermann; Ninad R. Bondre; John A. Dearing; Lisa Deutsch; Shobhakar Dhakal; et al. (Ambio, 2012)

Exotic tree species displace indigenous ones on farms at intermediate altitudes around Mount Kenya - Katja Kehlenbeck; Roeland Kindt; Fergus L. Sinclair; Anthony J. Simons; Ramni Jamnadass (Agroforestry Systems, 2011)

Characterisation of polymorphic microsatellite markers isolated from Drakaea glyptodon Fitz. (Orchidaceae) - J. M. Anthony; R. D. Phillips; E. A. Sinclair; K. W. Dixon (Conservation Genetics Resources, 2010)

Ecological specialization in mycorrhizal symbiosis leads to rarity in an endangered orchid - NIGEL D. SWARTS; ELIZABETH A. SINCLAIR; ANTHONY FRANCIS; KINGSLEY W. DIXON (Molecular Ecology, 2010)

Characterisation of polymorphic microsatellite markers in the widespread Australian seagrass, Posidonia australis Hook. f. (Posidoniaceae), with cross-amplification in the sympatric P. sinuosa - E. A. Sinclair; J. Anthony; G. T. Coupland; M. Waycott; M. D. Barrett; R. L. Barrett; M. L. Cambridge; M. J. Wallace; K. W. Dixon; S. L. Krauss; G. A. Kendrick (Conservation Genetics Resources, 2009)

Effect of exercise mode on heart rate variability during steady state exercise - Anthony S. Leicht; Wade H. Sinclair; Warwick L. Spinks (European Journal of Applied Physiology, 2007)

The role of predation in the decline and extirpation of woodland caribou - Heiko U. Wittmer; Anthony R. E. Sinclair; Bruce N. McLellan (Oecologia, 2005)

Landscape scale, heterogeneity, and the viability of Serengeti grazers - John M. Fryxell; John F. Wilmshurst; Anthony R. E. Sinclair; Daniel T. Haydon; Robert D. Holt; Peter A. Abrams (Ecology Letters, 2005)
Species persistence can be threatened by substantial temporal variation in food resources over time. On the other hand, spatial heterogeneity in resources at the landscape scale might allow mobile consumers to compensate for temporal variability in resource availability at the local scale. We evaluated this hypothesis, using an extensive data set on foraging, grass growth, and movement by Thomson's gazelles living on the Serengeti Plains. Here we show that modelled populations of Thomson's gazelles can only persist under Serengeti conditions in the face of observed levels of rainfall stochasticity by making adaptive movements to take advantage of ephemeral spatial distributions of food resources. More importantly, our models suggest that Thomson's gazelles in Serengeti require unrestricted access to relatively large areas of grassland (> 1600 km 2 ) to guarantee long‐term persistence, particularly when there is positive spatial autocorrelation in resource abundance, as is the case in Serengeti. If this proves to be true for other species and/or other systems, then understanding of complex behavioural responses to spatially and temporally heterogeneous food supplies may be essential to successful conservation of grazing herbivores.

What limits the Serengeti zebra population? - Sophie Grange; Patrick Duncan; Jean-Michel Gaillard; Anthony R. E. Sinclair; Peter J. P. Gogan; Craig Packer; Heribert Hofer; Marion East (Oecologia, 2004)

Calcium in gravitropism. A re-examination - William Sinclair; Anthony J. Trewavas (Planta, 1997)